Optimization of CMT Welding Parameters of Stellite-6 on AISI316L Alloy Using TOPSIS Method - Thiagarajan, Thinesh Babu; D, Raguraman (International Journal of Integrated Engineering, 2023)
This article discusses the welding parameters optimization to find the quality of stellite-6 cladding on AISI304L austenite alloy using a new optimization method called Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The experiments (31 nos.) were carried out with the cold metal arc transfer welding method (CMT) based on the central composite design (CCD). The cladding material is the stellite-6 alloy which is appreciated for its corrosion and wear resistance. Four factors (welding current, voltage, welding speed and torch angle) and five levels were considered for the experiment and the optimization. It is necessary to find the optimized parameters for the industrial applications as a huge number of experiments are not recommended. The optimization results showed that the 2nd experiment had the 1st rank with high relative closeness and the 19th experiment was in the last rank. Higher current and low welding speed yielded good results and a low corrosion rate of 0.004582 mm/yr. Furthermore, the Micro-structural, Corrosion study and the SEM-EDS of the specimen produced by the 2nd experiment are discussed here. EDS study showed the presence of Cr and Co elements in the cladding region with maximum.